Avaliação da função renal em pacientes com doença pulmonar obstrutiva crônica através de biomarcadores - Andrade, Natalia Morais de (2016)
Chronic Obstructive Pulmonary Disease (COPD) is characterized by airflow obstruction caused by inhaling toxic particles and gases. Patients affected by COPD present many comorbidities, such as chronic kidney disease (CKD). Objective. To access renal function in patients with COPD through new biomarkers. Methodology. Was conducted a prospective study with 36 patients followed in two hospitals in the city of Fortaleza / CE - Brazil. General data and clinical trials and laboratory evaluation, assessment of renal function was estimated glomerular filtration rate (GFR) and new biomarkers were evaluation. Neutrophil gelatinase-associated lipocalin was quantified in blood and urine; Monocyte chemotactic protein (MCP-1) was quantified in urine and Galectin-3 was quantified in blood. Results. Changes in the values of GFR that showed higher in the COPD group than in the control group. Similar results were found with albumin values. Nevertheless, the figures showed no overt kidney damage. Evaluation of biomarkers only the MCP-1 and galectin-3 met with high levels in the study group. Association with renal dysfunction parameters (TFG) and pulmonary (FEV1) in COPD group, only galectin-3 showed a strong inverse association. Conclusion. COPD patients have a kidney disease diagnosed by the expression of biomarkers. Thus, the use of new biomarkers is of great importance for the diagnosis of subclinical or underdiagnosed CKD.